ANALISIS YURIDIS PERLINDUNGAN YURIDIS HAK ULAYAT MASYARAKAT ADAT CIPTAGELAR PASCA PENGESAHAN UNDANG-UNDANG CIPTAKERJA (UUCK) DAN PENGAKUAN UNESCO TERHADAP KAWASAN GEOPARK CILETUH, SUKABUMI - Endah Pertiwi; Nuchraha Alhuda (Jurnal Hukum Lex Generalis, 2024)
In 2018 the Ciletuh-Palabuhanratu Geopark, Sukabumi Regency received Global recognition from the United Nations Educational, Scientific and Cultural Organization (UNESCO), UNESCO Global Geoparks are defined as an integrated geographical area where international geological sites and landscapes are managed with the concept of holistic protection. The existence of Indigenous Peoples in the forest area will be related to the forest. Customary law communities in forest areas can use forest, even Article 37 of the Forestry Law regulates customary forests. According to its function. Constitutional Court Decision No. 35/PUU-X/2012, based on the judicial review, it is hoped that there will be no more problems related to forest status between customary law communities and the state or companies. In fact, in the life of the Ciptagelar kasepuhan community there is still overlapping of laws. From this, problems arise (1) How is the management of the customary land of the Ciptagelar community in the Ciletuh Geopark area, (2) What are the rights for the Ciptagelar community in the Ciletuh Geopark area, (3) How is the management of land conflict resolution between indigenous peoples, indigenous peoples and the government? regional and national, and indigenous peoples and corporations. This study uses a combined Normative and Empirical research method with the Statute Approach, Analytical and Conceptual Approach, Case Approach and perceptual approach. The results of this study are that so far, there have been many regional regulations in regencies/cities, provinces that give recognition to Indigenous Peoples, Indigenous Peoples who carry out their traditional work have the potential to lose their land. This happens because the Job Creation Law generally regulates the ease of investing. There is still a lack of guarantees for customary rights to control their customary areas if they are clashed with the principle of public interest by the government. Until now, there is no legislation that is lex specialist for the protection of the rights of indigenous peoples.